Contribution to the knowledge of the Hungarian Oribatida fauna (Acari) II - Mahunka-Papp, L.; Mahunka, S. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2007)
Collecting at several sites in Hungary yielded six Oribatida species rare in Hungary [Verachthonius diversus Moritz, 1976, Damaeolus ornatissimus Csiszár, 1962, Berniniella setilonga Iturrondobeitia et Salofia, 1988, Suctobelba discrepans Moritz, 1970, Suctobelbella messneri Moritz, 1971, Bipassalozetes striatus (Mihelčič, 1955)] and two new to the science (Amerioppia hortensis, Urubambates xerophilus spp. n.). These results complement the knowledge of Hungarian oribatids and the distribution data in their catalogue published earlier (Mahunka and Mahunka-Papp 2004). Synonymies of some earlier described species from Hungary are given. With 16 figures.